2017
DOI: 10.1253/circj.cj-17-0154
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Long-Term Outcomes of Mechanical and Bioprosthetic Aortic Valves ― A Propensity Score Analysis ―

Abstract: of age, either type of valve prosthesis can be chosen. The aim of this study was to assess the mortality and valverelated complications and compare the long-term outcomes of mechanical vs. bioprosthetic valves in Japanese patients undergoing aortic valve replacement (AVR) stratified into 3 age groups (<60 years; 60-69 years, and ≥70 years). Methods PatientsThis study was a pooled analysis of 2 large retrospective T he American College of Cardiology/American Heart Association (ACC/AHA) recently published their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…One of the greatest merits of mechanical valves is greater freedom from reoperation, especially in younger patients. [29][30][31] In contrast, reoperation due to SVD in bioprosthetic valves is always a concern. In this study, we found that the incidence of SVD in bioprosthetic valves was only 2.0% in patients on hemodialysis, and the reoperation rate due to SVD and other reasons among patients on hemodialysis was not particularly high at approximately 2% to 3% within 5 years of surgery in both group M and group B.…”
mentioning
confidence: 99%
“…One of the greatest merits of mechanical valves is greater freedom from reoperation, especially in younger patients. [29][30][31] In contrast, reoperation due to SVD in bioprosthetic valves is always a concern. In this study, we found that the incidence of SVD in bioprosthetic valves was only 2.0% in patients on hemodialysis, and the reoperation rate due to SVD and other reasons among patients on hemodialysis was not particularly high at approximately 2% to 3% within 5 years of surgery in both group M and group B.…”
mentioning
confidence: 99%
“…AVR, aortic valve replacement AVR with mechanical valves compared to those with bioprosthetic valves. 8,[10][11][12][17][18][19] In the present study, there were no differences between the two groups in survival as well as cardiac mortality-free survival. No significant differences were found in overall survival as well as cardiac mortality-free survival between patients who underwent AVR with biological prosthesis and mechanical prosthesis in the present study.…”
Section: Commentmentioning
confidence: 66%
“…Several studies also have revealed mechanical valves to be superior to bioprosthetic valves in terms of survival in these aged group of patients 5,9,13,14,16 . Other studies, however, have failed to demonstrate superiority in terms of survival in the patients who underwent AVR with mechanical valves compared to those with bioprosthetic valves 8,10–12,17–19 …”
Section: Commentmentioning
confidence: 99%
“…On the other hand, in the Edinburgh trial, Oxenham et al (5) conducted a prospective randomized study in which they found no differences in the 20-year survival rate between mechanical and bioprosthetic valves. Similarly, McClure et al (6) and Minakata et al (7) reported that there was no difference in overall survival between the two types of valves. In contrast, with the slightly controversial statement regarding the survival, it seems that there is an agreement of most of the studies that the major bleeding events are more common in MVs.…”
mentioning
confidence: 87%